Strengthening and promoting digital health practice: results from a Global Digital Health Partnership’s survey - Cascini, Fidelia; Gentili, Andrea; Causio, Francesco Andrea; Altamura, Gerardo; Melnyk, Andriy; Beccia, Flavia; Pappalardo, Ciro; Lontano, Alberto; Ricciardi, Walter (Frontiers in Public Health, 2023)
Background & Objective The capacity to promote and disseminate the best evidence-based practices in terms of digital health innovations and technologies represents an important goal for countries and governments. To support the digital health maturity across countries the Global Digital Health Partnership (GDHP) was established in 2019. The mission of the GDHP is to facilitate global collaboration and knowledge-sharing in the design of digital health services, through the administration of surveys and white papers. Objective The scope of this study is to critically analyze and discuss results from the Evidence and Evaluation GDHP Work Stream’s survey, understand how governments and countries intend to address main obstacles to the digital health implementation, identify their strategies for a communication of effective digital health services, and promote the sharing of international based best practices on digital health. Methods This survey followed a cross-sectional study approach. A multiple-choice questionnaire was designed to gather data. Choices were extracted from research publications retrieved through a rapid review. Results Out of 29 countries receiving the survey, 10 returned it. On a scale from 1 to 5, eHealth systems/platforms (mean = 3.56) were indicated as the most important tool for centralized infrastructure to collect information on digital health, while primary care (mean = 4.0) represented the most voted item for healthcare services to collect information on digital health. Seven Countries out of 10 identified lack of organization, skepticism of clinicians, and accessibility of the population as a barriers to adopt digital health implementation, resulting to be the most voted items. Finally, the most endorsed priorities in digital health for Countries were the adoption of data-driven approaches (6 Countries), and telehealth (5 Countries). Conclusion This survey highlighted the main tools and obstacles for countries to promote the implementation of evidence-based digital health innovations. Identifying strategies that would communicate the value of health care information technology to healthcare professionals are particularly imperative. Effective communication programs for clinicians and the general population in addition to improved digital health literacy (both for clinicians and citizens) will be the key for the real implementation of future digital health technologies.